Duodenal cryptococcus infection in an AIDS patient. Issue 3 (March 2015) - Li, Jiamin; Wang, Ningfang; Hong, Qunying; Bai, Chunxue; Hu, Bijie; Tan, Yunshan
<x xml:space="preserve">Abstract</x> Cryptococcal infection primarily affects the lung or the central nervous system and rare cases have been reported involving the gastrointestinal tract. However, among patients with HIV/AIDS, the gastrointestinal involvement is increasing. According to the PubMed search results, there were seven cases reported involving duodenal cryptococcosis combined with AIDS in five reports. Here, we report the case of a patient found to have AIDS combined with duodenal, pulmonary, and subsequent neurological cryptococcal infection simultaneously. The duodenal cryptococcosis was diagnosed on the basis of PET/computed tomography, which showed intense captation of glucose metabolism in duodenum (maximum standardized uptake value 16.53); a positive serum cryptococcal latex agglutination test; and upper gastrointestinal endoscopy-guided duodenal biopsy that confirmed Cryptococcus neoformans yeast. The patient's HIV screen test was positive. Because of refusal of lumbar puncture and the difficulty of performing transbronchial lung biopsy, the pulmonary and neurological involvements were the only clinical diagnoses. This case indicates that when cryptococcosis exists in a rare location, AIDS should be considered and when cryptococcosis occurs in the HIV-infected patient, disseminated disease is more common.